2020
DOI: 10.33988/auvfd.624047
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lactic acid bacteria inoculant on quality, fermentation profile and nutritive value of alfalfa silage at different ensiling period

Abstract: The present study was carried out to investigate the effects of lactic acid bacteria inoculant on quality, fermentation profile and nutritive value of alfalfa silage at different fermentation periods. After harvesting, fresh alfalfa samples were packed into polyethylene film and the commercial lactic acid bacteria inoculant was used as silage additive. Totally of 21 silage packages were opened by weekly for the analysis. Smell, color, structure, and total scores of alflalfa silage were significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The high sugar content of silages allows fermenting of them by the LAB population of silages and yielding lower pH results. The decrease in pH has also been reported by Filya and Sucu (2007) and Aktürk and Gümüş (2020).…”
Section: Discussionsupporting
confidence: 84%
“…The high sugar content of silages allows fermenting of them by the LAB population of silages and yielding lower pH results. The decrease in pH has also been reported by Filya and Sucu (2007) and Aktürk and Gümüş (2020).…”
Section: Discussionsupporting
confidence: 84%
“…Our study determined that the lowest pH levels during the 60th-day fermentation were in Group A (14.86%) (Table 4). In comparison, the highest NH 3 -N level was found in Group A, with 9.08%, which was significantly higher than the other groups (p < 0.017) (Table 7) (Aktürk & Gümüş, 2020). This situation has shown that adding sumac and molasses (Yakisir & Aksu, 2019) reduces proteolysis in silage fermentation, thereby partially reducing the formation of undesirable NH 3 -N in silage and positively affecting silage fermentation.…”
Section: Discussionmentioning
confidence: 90%
“…It was also reflected in the physical properties of the silages. The lowest Flieg scores of the silages were determined in the A group and significantly lower than the other groups ( p < 0.01) (Aktürk & Gümüş, 2020). Proteins are hydrolyzed to peptides, amino acids and ammonia by plant proteases and microbial activity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Whipped cream added to silage caused a decrease in the NDF content of alfalfa silage. The cell wall contents (ADF, NDF) of silage are important quality parameters, which affect the digestibility of alfalfa silage and animal performance (Aktürk, & Gümüş, 2020). Considering at DDM, DMI, RFV of the alfalfa from which the silages are made, it is seen that all silages except the control group have an advantage over dry grass.…”
Section: Table 3 Fermentation Quality Of Alfalfa Silagesmentioning
confidence: 99%